Health Informatics at the University of Victoria - Protti, D.; Fisher, P. (Yearbook of Medical Informatics, 1996)
The University of Victoria has the only program in Canada offering a Bachelor of Science degree in Health Information Science. To meet the requirements of the degree, students must complete 60 units of course work (normally 40 courses) and 4 CO-OP work terms over 4.3 years. The School admits approximately 30 students each year. Seventy-five percent of the students come from British Columbia, ranging in age from 18 to 50 years with the average age being 26 years. In addition to recent high school graduates, over 40% have previous degrees or diplomas, and 65% have over 5 years of work experience. The School’s teaching team consists of 4 full-time faculty, 2 professional staff, 2 clerical staff, 7 adjunct faculty and a variable number of sessional teaching staff. The majority of the faculty have health backgrounds, totalling 150 person-years of health care experience. As of November 1995, the School had 168 graduates 75% of whom are employed in British Columbia, 17% in other parts of Canada and 8% outside the country. Sixty-five percent of the graduates work in government departments including community health agencies; 10% work in hospitals, 20% work for management consulting firms, software houses, or computer hardware firms, and 5% are otherwise employed. Almost 100% of the graduates are gainfully employed in professional positions in which their health information science degree is valued. They work as systems analysts, system designers/developers, consultants, research assistants, health-care planners, information system-support staff/trainers and client-account representatives. Some are already in senior management positions.
Keywords: Health Information Science; Health Informatics; Computers in Health Care; Curriculum; Education; Training